Financial and Statistical Analysis of Investment Projects High-Tech Scientific Developments Based on Carbon Nanomaterials - Motsnyi, F. V.; Sinytskyi, M. E. (Statistics of Ukraine, 2017)
Carbon nanomaterials (graphene, nanotubes, fullerenes, the family of derivatives from C ) belong to the miraculous materials of 21 century, which can radically change technologies in the coming years. Thus, unique supercapacitors with the capacity of 10.000 F have been proposed on their basis, which is 12.5 thousand higher than the capacity of the Earth. Immense funds have been invested globally in research of carbon nanomaterials and development of devices on their basis. Utilization of scientific advancements in the domestic industry will promote economic growth, innovation society building and market recovery in Ukraine. This article is the first to pose the question about selection of advanced developments projects on the basis of carbon nanomaterials using Monte Carlo method. Investment projects for high tech scientific developments (nanotubes, nanobatteries, supercapacitors, nanoaccumulators) are analyzed. Approaches to account for the risks of investment projects in the conditions of non-established stock market in Ukraine are shown. Use of Monte Carlo method as the most preferred approach to evaluating the impact of risks on decision-making in the conditions of uncertainty is substantiated. Current market prices on respective products are used as the input database. The Net Present Value (NPV) and the probability of its negative numbers are computed. The point of the project reliability at which the probability of negative NPV numbers approximates zero is found. It is shown that this point can be used as the benchmark, because the relative distance to it is the criterion for selection of the most acceptable version of project implementation. The projects with minimal expected risks of implementation are selected.